BOSHLANG'ICH SINF O'QUVCHILARINING NUTQ MADANIYATINI SHAKLLANTIRISH METODIKASI - Ochilova Fayyoza Mansurovna (TADQIQOTLAR.UZ, 2024)
Annotation: the main task of primary class mother tongue classes is to prepare students for educational activities, to form a person who can enter into communication with others, to convey his opinion in a way that is understandable to others.